Bronchial responses to substance P after antigen challenge in the guinea-pig: in vivo and in vitro studies - E. Boichot; V. Lagente; G. Le Gall; C. Carré; J. M. Mencia-Huerta; P. Braquet; A. Lockhart; N. Frossard (Mediators of Inflammation)
The effect of antigen challenge on the airway responses to substance P and on the epithelial neutral endopeptidase (NEP) activity was investigated in aerosol sensitized guinea-pigs. In vivo, bronchial responses to aerosolized substance P were similar to the responses observed in antigen-challenged guinea-pigs and in the control groups. In contrast, when the guinea-pigs were pretreated with the NEP inhibitor, phosphoramidon, a significant increase in the airway responses to substance P was observed after antigen challenge in vivo. However, in vitro, the contractile responses of the tracheal smooth muscle to substance P were similar between groups of guinea-pigs, in respect to the presence or absence of the epithelium and/or phosphoramidon. Histological studies showed an accumulation of eosinophils in the tracheal submucosa after antigen challenge and intact epithelial cells. These results show that in vivo bronchial hyperresponsiveness to substance P after antigen challenge in the guinea-pig is not associated with increased responses of the smooth muscle to exogenous SP in vitro. In addition, the results with phosphoramidon suggest that loss of NEP activity cannot account for the in vivo bronchial hyperresponsiveness to substance P presently observed.